Physics teachers’ difficulties in teaching introduction to quantum physics in senior high school - Putri Paransucia; Irma Fitria Amalia (Research in Physics Education, 2022)
The High School Physics curriculum would not be complete without some basic concepts of Quantum Physics. The basic concepts of Quantum Physics are attractive to students, but the material is challenging to teach. This is because the phenomenon of Quantum Physics experienced by students is different from the real world and many principles of Quantum Physics may not be in accordance with the ideas that students know. Although the results of previous studies revealed a lot of research on the context of students' understanding of the concepts of Quantum Physics. However, limited empirical data regarding the difficulties of high school teachers in teaching quantum physics are still rarely encountered in physics education research. This study aims to explore data on the difficulties of high school physics teachers in teaching quantum physics concepts. This research design uses quantitative and qualitative case study methods. To get three participants, namely 3 twelfth grade high school physics teachers, the researcher used a purposive sampling technique. The age range of participants is between 45-55 years while the teaching experience of teachers ranges from 10 to 30 years. The instruments used in this study were a questionnaire and a semi-structured interview protocol. In this study, the questionnaire analysis used descriptive statistical analysis, while the interview data analysis used thematic analysis. The results of the study revealed that high school physics teachers had difficulty understanding the concept of quantum physics, and had little difficulty in determining the right pedagogical approach, conducting laboratory activities, and building an evaluation system.